Analyzing Cost Accounting Methods In Light of Technological Development and Their Impact on Managerial Decision-Making - Maytham Abbas Khudhair Al-Salmawi; Hasanain Salim Rasheed; Hussein Falah Hasan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The objective of this study is to highlight the role of information technology in improving decision-making at the General Company for Electrical Industries in Baghdad. To achieve the study’s objectives, a questionnaire consisting of 30 items was prepared and distributed to department heads and specialized employees. The data was analyzed using the SPSS. This study concluded that analyzing cost accounting methods considering technological development is one of the most important approaches for providing the necessary information to solve problems. Additionally, information technology facilitates communication, coordination, and the exchange of information between various departments and the external environment, while also providing accurate, appropriate, and sufficient information at the right time, thereby contributing to an improved decision-making process.